Kepastian Hukum dan Upaya Pertanggungjawaban Pemerintah Terhadap Perlindungan Hak Tanah Ulayat di Pulau Rempang - Nadifa Keyla Ismail; Novita Fitria Azzahra; Farchanza Haykanna Pireno; Fitrya Putry Amanda; Jessika Stefany Dyana; Diani Sadia Wati (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The State of Indonesia regulates constitutionally in the 1945 Constitution all elements in the territory of Indonesia, including the elements of land and sea with their natural wealth, which is very influential for the survival of human life. So far, the law that was supposed to be the umbrella of the law that guarantees the realization of a subject set in it has not gone as it should. This is demonstrated by the escalation of the agrarian conflict in Rempang Island, Batam, related to the rights to land belonging to indigenous communities that were deprived of land use in the National Strategic Project of Eco City Reservoir. The study aims to analyze the role of law in Indonesia in the settlement of the conflict. The research methods we use are qualitative methods through the study of literature and normative legal (legal) research. Literature studies involve the collection of data sources through journals, articles, news portals, and relevant books related to the research topics taken. Normative legal research is aimed at finding the truth about the existence of legal certainty. The results of our research will show how the existing laws in Indonesia regulate the agrarian conflict on Rempang Island and how the government's efforts to take policy by advancing the laws that have been established in Indonesia for the survival of the rights of indigenous peoples affected by the conflict.